Specific stimulation of lymphocytes from patients with AIDS by herpes simplex virus antigens. - Wainberg, M A (1987)
Peripheral blood lymphocytes of patients with AIDS are generally anergic to stimulation by lectins or by alloantigens. We have succeeded in demonstrating that the lymphocytes of six AIDS patients, with histories of herpes simplex virus (HSV)-induced genital, anal and/or oral lesions, retained functional specificity with regard to HSV antigens. This was accomplished by treating patient lymphocytes with OKT8 monoclonal antibodies, in the presence of complement, to yield a cell population that was partially responsive to phytohaemagglutinin (PHA). Enhanced proliferation was obtained in the presence of exogenous interleukin-2, which was also employed to foster the growth of these cells over several generations. Lymphocytes derived from these AIDS patients, and maintained in vitro as described, were specifically stimulated in proliferation assays by a HSV antigen preparation in six of the ten cases studied.